2003
DOI: 10.3136/fstr.9.54
|View full text |Cite
|
Sign up to set email alerts
|

Trace Volatile Components in Essential Oil of Citrus sudachi by Means of Modified Solvent Extraction Method

Abstract: Sixty-five grams of sudachi (Citrus sudachi Hort. ex Shirai) essential oil from 18 kg of peel was isolated by a modified solvent extraction (MSE) in a semi-preparative scale with a hand-screw pressing instrument and a solution of pentane and dichloromethane. Twenty-four compounds were newly identified. The essential oil retained its original aroma without any off-flavor. The odor character of sudachi essential oil prepared by MSE method was described by means of odor impact spectra (OIS). The combination of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
3
0
5
Order By: Relevance
“…by A = mass spectrum and linear retention indices agreed with the standards; B = mass spectrum and linear retention indices agreed with the literature data10,11) RI = Linear Retention Indices on DB-wax and DB5-MS column (60 m 0.25 mm 0.25mm) as a homologous series of n-alkanes (C7-C25).…”
supporting
confidence: 79%
“…by A = mass spectrum and linear retention indices agreed with the standards; B = mass spectrum and linear retention indices agreed with the literature data10,11) RI = Linear Retention Indices on DB-wax and DB5-MS column (60 m 0.25 mm 0.25mm) as a homologous series of n-alkanes (C7-C25).…”
supporting
confidence: 79%
“…Mookdasanit et al reported that diisopropyl disulfide, a sulfur‐containing compound, was identified as one of the odour‐active components of Sudachi peel aroma . Yang et al also reported that saturated aliphatic aldehydes such as decanal and dodecanal and esters, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Safayhi et al (1994) O maior valor de concentração já atribuído ao -farneseno como componente do óleo essencial de camomila alemã foi de 24,2%, enquanto que para o isômero α a maior concentração já relatada foi de 8,7% (Ayoughi et al, 2011). O aroma de ambos pode ser descrito como floral fresco e atribui-se, também a ambos, limiares de odor em água de 87 µg L -1 (Mookdasanit et al, 2003;Tamura et al, 1999). É muito provável que a influência do - O espiroéter (eno-ino-dicicloéter ou chamo-espiroéter) é um terpeno característico da camomila e pode representar até cerca de 26,1% da composição de seu óleo essencial (Orav et al, 2010).…”
Section: Composto Propriedades Farmacológicasunclassified
“…O α-pineno possui aroma agudo e penetrante de pinho, floral, tipo erva e madeira de cedro (Mookdasanit et al 2003;Tamura et al, 1999). Esse composto possui um baixo limiar de odor em água (6,0 µg L -1 ) e já foi encontrado no óleo essencial da camomila alemã em concentrações de até 11,75% (Buttery et al, 1974;Borsato et al, 2008) causadoras de endocardite infecciosa (Leite et al, 2007).…”
Section: Composto Propriedades Farmacológicasunclassified